EFEKTIVITAS HUKUM UU NOMOR 1 TAHUN 2024 DALAM PENANGGULANGAN KEJAHATAN CYBERCRIME DI INDONESIA - Muh. Chaerul Anwar; Andi Dewi Pratiwi; Muh. Arfhani Ichsan (Al-Adl : Jurnal Hukum, 2026)
method by examining the prevailing regulatory framework under the UU ITE and its preventive mechanisms against cybercrime. The focus of this research lies in the tools and instruments employed in the implementation of these regulations, including cyber monitoring technologies and capacity building for law enforcement agencies. The findings indicate that although there has been a decline in certain types of cybercrime, such as phishing, incidents of data breaches have increased. Amendments to the provisions of the UU ITE have contributed to clearer legal protection and a more balanced approach between safeguarding freedom of expression and protecting individual rights. Despite advancements in the structure of law enforcement, significant challenges persist, particularly with regard to limited regional capacity, uneven infrastructure development, and low levels of public digital literacy. This study further highlights the importance of periodic regulatory updates and international cooperation in addressing cybercrime that is increasingly complex and transnational in nature. Strengthening the legal system and enhancing public awareness are therefore identified as key factors in fostering a safer digital environment and supporting sustainable growth of the digital economy.